2004
DOI: 10.1128/jb.186.17.5834-5841.2004
|View full text |Cite
|
Sign up to set email alerts
|

Hypercyst Mutants in Rhodospirillum centenum Identify Regulatory Loci Involved in Cyst Cell Differentiation

Abstract: Rhodospirillum centenum is a purple photosynthetic bacterium that forms resting cyst cells when starved for nutrients. In this study, we demonstrate that chalcone synthase gene (chsA) expression is developmentally regulated, with expression of chsA increasing up to 86-fold upon induction of the cyst developmental cycle. Screening for mini-Tn5-induced mutants that exhibit elevated chsA::lacZ expression has led to the isolation of a set of R. centenum mutants that display increased chsA gene expression concomita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 30 publications
1
57
0
Order By: Relevance
“…All the isolates were having capability of forming microcysts. Transition into cyst-like cells were observed in older cultures of Azospirillum was reported by Berlman (2004). Extracellular capsule was present in all 54 isolates which is in confirmity with reports of Madi et al, (1988).…”
Section: Morphological Characteristicssupporting
confidence: 79%
“…All the isolates were having capability of forming microcysts. Transition into cyst-like cells were observed in older cultures of Azospirillum was reported by Berlman (2004). Extracellular capsule was present in all 54 isolates which is in confirmity with reports of Madi et al, (1988).…”
Section: Morphological Characteristicssupporting
confidence: 79%
“…Multidomain proteins encoding a PYP domain have been discovered in a number of other bacteria (111), the most well-characterized being Ppr of Rhodospirillum centenum . This hybrid photoreceptor encodes a blue-absorbing PYP domain coupled to a red-absorbing bacteriophytochrome domain (56), and regulates the development of starvation-resistant cysts (9). Recent characterization of Ppr from Rhodocista centenaria provides evidence that this hybrid photoreceptor also functions in the chemotaxis signaling pathway (65).…”
Section: The Structural Basis Of Ligand Binding In the Pas Domain Familymentioning
confidence: 99%
“…Only a few bacterial species have been observed to make cysts. Initial studies of cyst formation in Rhodospirillum centenum and Azospirillum brasiliense identified a few genes (4,88) that are involved in the regulation of encystment in these bacteria. Genes similar to these regulators, however, have not been found in the A. vinelandii genome.…”
Section: Vol 191 2009mentioning
confidence: 99%